Anísio Teixeira e a Psicologia: o valor da mensuração - Bortoloti, Karen Fernanda [UNESP]; Cunha, Marcus Vinicius Da (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira, 2013)
This article analyzes the ideas and the work of Anísio Teixeira in the 1920s and 1930s, focusing on his views about the value of measurement for educational reform in Brazil. Considering that the thinking and practices of Teixeira should be understood in the context in which it was developed, the study presents the history of the presence of psychological knowledge in education, with special attention to the entrance of the Psychometrics in the New School movement. The paper concludes that, by defending the use of measurement, Teixeira has remained true to the goal of the New School that required to diagnoses scientifically the school universe, which was necessary to respond to the growing demand for schooling and the educational disabilities of the Brazilian educational institutions.

Analisa as ideias e a atuação de Anísio Teixeira nos anos 1920 e 1930, focalizando as suas concepções acerca do valor da mensuração para a renovação educacional no Brasil. Considerando que o pensamento e as práticas de Teixeira devem ser compreendidos no contexto em que se desenvolveram, apresenta um histórico da inserção dos saberes psicológicos na educação, com especial atenção para a adesão do movimento escolanovista à Psicometria. Conclui que, ao defender o uso da mensuração, Teixeira se manteve fiel à meta da Escola Nova que exigia diagnosticar cientificamente o universo escolar, o que se fazia necessário para responder à crescente demanda por escolarização e às deficiências das instituições de ensino brasileiras.
Anísio Teixeira and Psychology: the value of measurement
Keywords: história da educação brasileira; Escola Nova; Anísio Teixeira; Psicologia; Psicometria; History of Brazilian Education; New School; Anísio Teixeira; Psychology; Psychometrics